The Effectiveness of Administrative Sanctions as an Alternative to Criminal Law Enforcement in the Environmental Sector - Kurdi, Kurdi; Armansyah, Armansyah; Teuku Ahmad Dadek (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The escalating intensity of environmental violations in Indonesia necessitates the strengthening of effective law enforcement mechanisms, particularly following the enactment of the Job Creation Law and Government Regulation No. 22 of 2021, which redefined administrative sanctions as the primum remedium. This study examines the evolution of administrative legal instruments within the environmental law enforcement system and assesses the effectiveness of administrative sanctions—including government coercion and administrative fines—in preventing and addressing environmental violations. The research employs a normative–empirical juridical approach through regulatory analysis, case studies, and interviews with regional environmental inspectors. The findings reveal that administrative sanctions are implemented more swiftly, align more closely with the principles of ecological restoration, and exert a stronger influence on the economic motivations of violators compared to criminal sanctions. Nevertheless, their effectiveness remains constrained by limited human resources, inadequate supervisory budgets, and weak regional political commitment. The study concludes that administrative instruments hold a strategic role as the primary mechanism for environmental law enforcement, yet require institutional strengthening and integrated policy support to operate optimally.